Signal processing approaches for optimum planning in intensity-modulated radiotherapy - Sabbir Uddin Ahmad (2008)
The objective is to find a feasible solution to the problem of intensity modulated radiotherapy in order to determine or estimate the most appropriate intensity modulated beams (IMB) so that external beams match exactly the high dose region in the target volume and the prescribe target contour, whereas the normal unaffected organs remain within safe dose limits.